Functional variability in the flight phase of one metre springboard forward dives - Sayyah, M.; Hiley, M. J.; King, M. A.; Yeadon, M. R. (Human Movement Science, 2018)
In springboard diving, low variability in takeoff conditions and in the somersault orientation angle at water entry is to be expected since consistency and accuracy are necessary for a good dive. A diver`s adjustment of body configuration during flight may be a deliberate compensation for variations in takeoff conditions, leading to increased joint angle variability and decreased entry angle variability. The aim of this research was to investigate the extent to which a diver pre-plans the aerial phase and then makes adjustments in flight to control the entry angle in one metre springboard forward dives. Performances of 15 forward pike dives and 15 forward 2½ somersault pike dives, performed by an international diver were video recorded at 250Hz. Joint centres during flight were digitized and their spatial coordinates were subsequently reconstructed using the Direct Linear Transformation in order to determine orientation and configuration angles. A computer simulation model was used to investigate the effects of variability in takeoff conditions and configuration variability in flight on the variability of the orientation angle at water entry. The amount of variation in the somersault orientation angle at entry as determined using simulations based on the variability in the takeoff conditions was four times greater than the variation in the recorded performances. It was concluded that the diver used open loop control for the first half of the flight phase and subsequently used feedforward and feedback control to make timing adjustments of hip and arm angles to reduce the variability of his entry orientation angle. AUTORREFERAT